Emerging market sovereign debts as a means for profit maximization and portfolio diversification - (:unkn) unknown (IGI Global, 2017)
The case for emerging markets debts (EMD) has convinced many investors. This is an asset class that has been experiencing an increase in inflows and is getting international investors attention. During the past two decades, cross-border inflows into 'emerging market' debt instruments have rose rapidly. Over twelve trillion dollar is currently invested in 'Emerging Markets' debt. This asset classes has delivered strong returns over time and deserves consideration. Therefore, this paper is intended to show how and why Emerging Market debts are vital instrument in portfolio diversification by using descriptive analysis. The performance assessment has made by noting the unique statistical attributes of 'emerging market' bond returns, such as their correlation with other asset classes and also by taking their annualized volatility rate and Sharpe ratios. The assessment has done based on compiled data from known sources such as JP Morgan, Bloomberg and other well known secondary data sources. © 2017, IGI Global. All rights reserved.